Radiological and Clinical Outcomes of the Dovetailed Notch Scarf Osteotomy for Correcting the First Metatarsal Pronation in Moderate to Severe Hallux Valgus Deformity: A Comparative Study - Ming-Zhu Zhang MD, PhD; Chao Wang MD (Foot & Ankle Orthopaedics)
Category: Bunion; Midfoot/Forefoot Introduction/Purpose: The traditional scarf osteotomy (TSO) has limited ability to correct the first metatarsal pronation. A novel modification which we refer to as a “dovetailed notch Scarf osteotomy” (DNSO) has been developed to enhance the ability to correct coronal plane pronation. The study aimed to observe and compare TSO to DNSO in the treatment of moderate to severe hallux valgus deformity. Methods: This retrospective study included 78 feet that had a TSO and 105 feet that had a DNSO.Minimum follow-up was 24 months.Weightbearing CT (WBCT) and weightbearing anterior-posterior (AP) radiographs were taken preoperatively and at the last follow-up. We measured the intermetatarsal angle (IMA), hallux valgus angle (HVA), distal metatarsal articular surface angle (DMAA) on AP radoigrpahs and first metatarsal coronal pronation angle (α angle), tibial sesamoid coronal grading (TSCG), and first metatarsal length (FML) on WBCT. Clinical assessment was done using Visual Analogue Scale (VAS), American Orthopaedic Foot and Ankle Society (AOFAS), Foot and Ankle Ability Measure (FAAM), and the 36-Item Short Form Health Survey (SF-36). The occurrence of postoperative complications was also documented. Results: The DNSO group exhibited a significantly higher correction amount of α angle and IMA (14.3±9.9° and 10.3±4.6°) than the TSO group (8.6±5.9 °and 5.4±5.9°) during the final follow-up assessment (P<.05).The DNSO group (10.1±6.9°and 4.8±3.1°) demonstrated significantly smaller α angle and IMA compared to the TSO group (15.3±5.7°and 9.1±5.0°) at 24 months post-surgery (P<.05). (P<.05 ).The postoperative FAAM-ADL and SF-36-PF scores were significantly higher in the DNSO group (97.2±3.3 and 95.7±4.4 points) compared to the TSO group (92.3±3.3 and 87.7±8.7 points) (P<.05). Additionally, hallux varus occurred in one case in the DNSO group, while four cases were observed in the TSO group. Conclusion: Two osteotomy methods can effectively correct moderate to severe hallux valgus deformity. Compared with the TSO, the DNSO has stronger correction ability. The most crucial aspect lies in its controllability when correcting first metatarsal pronation, as well as its exceptional performance in addressing IMA.